Plant architecture without multicellularity: quandaries over patterning and the soma-germline divide in siphonous algae - Coneva, Viktoriya; Chitwood, Daniel H. (Frontiers in Plant Science, 2015)
Multicellularity has independently evolved numerous times throughout the major lineages of life. Often, multicellularity can enable complex, macroscopic organismal architectures but it is not required for the elaboration of morphology. Several alternative cellular strategies have arisen as solutions permitting exquisite forms. The green algae class Ulvophyceae, for example, contains truly multicellular organisms, as well as macroscopic siphonous cells harboring one or multiple nuclei, and siphonocladous species, which are multinucleate and multicellular. These diverse cellular organizations raise a number of questions about the evolutionary and molecular mechanisms underlying complex organismal morphology in the green plants. Importantly, how does morphological patterning arise in giant coenocytes, and do nuclei, analogous to cells in multicellular organisms, take on distinct somatic and germline identities? Here, we comparatively explore examples of patterning and differentiation in diverse coenocytic and single-cell organisms and discuss possible mechanisms of development and nuclear differentiation in the siphonous algae.